Gargalos e demandas da infraestrutura rodoviária e os investimentos do PAC: Mapeamento Ipea de obras rodoviárias - Carlos Alvares da Silva Campos Neto; Ricardo Pereira Soares; Ins\~a Melo Ferreira; Fabiano Mezadre Pompermayer; Alfredo Eric Romminger (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Acknowledged the importance of the Road transportation to Brazilian economy, especially when considering cargo transportation, Ipea has studied the main economical and institutional problems that involve Brazilian roads. Firstly, we present an overview of the road system from 1950's expansion to today's concessions and private-public partnerships' arguments. Following, we describe the financing model for this segment as well as the investments it's received - public and private - for expanding and operating. Afterwards, we present the major infra-structural demands, consolidating the Mapeamento Ipea de Obras Ferroviárias, followed by an analysis of how has the government program, PAC, been impacting over those needs. Next, we review Brazil's transport system division, analyzing the participation of road transport as it is now, and its perspectives for the next fifteen years. At last, we describe the general results of our analysis.
Keywords: L92; H42; H54; G18; 330; Straße; Infrastrukturversorgung; Öffentlich-private Partnerschaft; Brasilien